The Relationship Between Artificial Intelligence and Consumer Decision Making in the Context of Personalized Cosmetic Products - Nirmal, Sarika A.; Wani, Nalanda D. (The Scientific Temper, 2025)
Artificial intelligence, or AI, creates entirely new dimensions in combining consumer experiences via personal marketing instruments. This objective of the study is to explore the causal relationship between AI-based personalization and consumer behavior within the cosmetics sector. Further, the investigation looks into how AI acceptance and effectiveness in influencing purchase behaviour are dependent on factors such as digital literacy, demographic attributes, and trust. This study used a quantitative method with structured questionnaires, targeting women in Pune who have interacted with AI-based beauty applications. Data were analyzed on SPSS software by applying descriptive statistics, Cronbach’s Alpha for reliability, regression analysis, and ANOVA testing. The findings indicated a significant influence of AI personalization on consumer purchasing intent and trust. Digital literacy and ease of use were crucial for consumer engagement. Ethical and data privacy concerns were some of the barriers to hasty AI acceptance. The tendency of the cosmetic company to encourage and provide customer satisfaction and loyalty in a digital marketplace would be with transparency about ethical artificial intelligence use and user-centric personalization strategies.